Building health equity through housing policies: critical reflections and future directions for research. Issue 8 (14th June 2022) - Leifheit, Kathryn M; Schwartz, Gabriel L; Pollack, Craig Evan; Linton, Sabriya L
Abstract : Housing may be at once the most powerful and underused tool at our disposal to improve population health. Using examples from the USA, we argue that current levels of housing insecurity are the result of clear and inequitable policy choices, leading to the entrenchment of health inequities—particularly, across race and class. Solutions to housing insecurity must, therefore, be structural. The COVID-19 pandemic has opened a window of opportunity for these structural housing policy reforms. Through justice- and action-oriented research, health researchers can inform the development and implementation of housing policies that advance health equity. We offer a series of recommendations to better position our field to achieve this goal.